Importance of reservation services in tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Importance of Hotel Reservation. A reservation enhances the likelihood that the traveler will receive a better rate for ensured lodging when they arrive. Reservations help hotels to manage their guests’ experiences during slow and busy periods more effectively.